1991
DOI: 10.1121/1.400974
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivity to vowel continua in Old World monkeys (Macaca) and humans

Abstract: Previous studies indicate that monkey pure tone frequency discrimination is quantitatively and qualitatively very different from that of humans: Monkey DLs at 1.0 and 2.0 kHz are up to 20 times larger than human DLs, and monkeys DLs increase as sensation level increases, in contrast to human DLs [Sinnott et al., J. Acoust. Soc. Am. 78, 1977-1985 (1985); Sinnott et al., J. Comp. Psychol. 101, 126-131 (1987)]. These results led to an hypothesis that monkey frequency discrimination is more dependent upon "rate" c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Indeed, numerous other non-human animals spontaneously respond to formant shifts in their own species-typical vocalisations (Fitch and Kelley, 2000;Reby et al, 2005;Fitch and Fritz, 2006;Charlton et al, 2007a;Charlton et al, 2008;Charlton et al, 2010; and are capable of perceiving formant shifts in human speech sounds with a high degree of accuracy (Baru, 1975;Burdick and Miller, 1975;Hienz et al, 1981;Hienz and Brady, 1988;Sinnott, 1989;Dooling and Brown, 1990;Sinnott and Kreiter, 1991;Sommers et al, 1992;Hienz et al, 1996). It is also noteworthy that the inter-individual variation in formant spacing we report is high: the minimum and maximum formant frequency spacing values for the exhalation, initial inhalation and later inhalation phases of bellows corresponded to a 16%, 25% and 31% variation around the mean values of 796, 708 and 354Hz, respectively (see Table1).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous other non-human animals spontaneously respond to formant shifts in their own species-typical vocalisations (Fitch and Kelley, 2000;Reby et al, 2005;Fitch and Fritz, 2006;Charlton et al, 2007a;Charlton et al, 2008;Charlton et al, 2010; and are capable of perceiving formant shifts in human speech sounds with a high degree of accuracy (Baru, 1975;Burdick and Miller, 1975;Hienz et al, 1981;Hienz and Brady, 1988;Sinnott, 1989;Dooling and Brown, 1990;Sinnott and Kreiter, 1991;Sommers et al, 1992;Hienz et al, 1996). It is also noteworthy that the inter-individual variation in formant spacing we report is high: the minimum and maximum formant frequency spacing values for the exhalation, initial inhalation and later inhalation phases of bellows corresponded to a 16%, 25% and 31% variation around the mean values of 796, 708 and 354Hz, respectively (see Table1).…”
Section: Discussionmentioning
confidence: 99%
“…Psychophysical studies in humans and animals have investigated the spectral processing of broadband stimuli with parametrically varied spectral envelopes, especially formant position and modulation depth (e.g. Pick 1980;Festen & Plomp 1981;Yost 1982;van Veen & Houtgast, 1985;Shamma et al, 1992;Bernstein & Green 1987;Hillier and Miller, 1991;Sommer et al, 1992;Sinnott et al, 1976;Sinnott and Kreiter, 1991;Supin et al, 1994;Amagai et al, 1999;O'Connor et al, 2000). However, no attempt had been made to link psychophysical measurements with neurophysiological properties of cortical neurons.…”
Section: Psychophysics Of Ripple Spectramentioning
confidence: 99%
“…Estimating the ability of the auditory system to resolve changes in formant frequency is a first step in understanding speech processing in the auditory system. Psychophysical experiments have estimated formant-frequency discrimination ability (Flanagan, 1955;Mermelstein, 1978;Sinnott and Kreiter, 1991;KewleyPort and Watson, 1994); however, reported thresholds of the formant-frequency discrimination tasks have differed among studies because of the complexity of the stimuli and differences in experimental procedures. For example, Mermelstein (1978) found that the threshold for discriminating changes in the first formant at 350 Hz was 50 Hz, which is much higher than the result of Flanagan (1955), who reported discrimination thresholds for the first formant (at 300 Hz) of 12 to 17 Hz.…”
Section: Introductionmentioning
confidence: 99%